Glutamate Ionotropic Receptor Kainate Type Subunit 3 (GRIK3) promotes epithelial‐mesenchymal transition in breast cancer cells by regulating SPDEF/CDH1 signaling. Issue 7 (11th April 2019) - Xiao, Bin; Kuang, Zhenzhan; Zhang, Weiyun; Hang, Jianfeng; Chen, Lidan; Lei, Ting; He, Yongyin; Deng, Chun; Li, Weiwei; Lu, Jingrun; Qu, Jing; Zhou, Quan; et al.
Abstract: Glutamate Ionotropic Receptor Kainate Type Subunit 3 (GRIK3) is an important excitatory neurotransmitter receptor that plays a significant role in various neurodegenerative diseases. However, the biological functions of GRIK3 in malignancies are largely unknown because of limited related studies. Here, we primarily reported that the expression of GRIK3 was higher in breast cancer tissues than in adjacent noncancerous tissues. GRIK3 expression was also positively correlated with the prognosis of patients with breast cancer. GRIK3 promoted the proliferation and migration abilities of breast cancer cells and enhanced the growth of orthotopically implanted tumors. Mechanically, GRIK3 influenced a range of signaling pathways and key signal transducers, including two epithelial‐mesenchymal transition regulators, SPDEF and CDH1. Heterogenous expression of SPDEF and CDH1 counteracted the migration and invasion abilities, respectively, of breast cancer cells induced by GRIK3. Moreover, overexpression of GRIK3 increased the expression of mesenchymal markers and decreased the expression of epithelial markers, resulting in the translocation of β‐catenin into the nucleus and the increased β‐catenin transcriptional activity. In conclusion, the present study reported a novel oncogenic role of GRIK3. Meanwhile, GRIK3, as a membrane receptor, may also serve as a potential therapeutic target for the treatment of breast cancer.